Miliary Tuberculosis and Infective Endocarditis - Gumasana, Harshil; Patel, Mansukh V (Global Journal of Medical and Clinical Case Reports, 2021)
Objective: To study the behaviour of Lumbar Lordosis (LL) after non-instrumented decompression surgery in patients diagnosed with Lumbar Spinal Stenosis (LSS). Methods and materials: Retrospective analysis of patients undergoing non-lumbar instrumented decompression surgery for lumbar spine stenosis, operated on between January 2011 and December 2017. The variables collected were age, sex, affected segment, and presence or not of degenerative spondylolisthesis (ELS). The Lumbar Lordosis (LL) parameter was analysed using conventional radiology in standing position pre and postoperatively. Results: 64 patients were selected, 17 women and 47 men, with an average age of 68 (35-83). 65% stenosis was located in a single level, and 39.1% had degenerative ELS grade I. The average follow-up was 26 months (6m-104m). A preoperative LL angle of 43.2º (9.8º-70.8º) and 47º (8º-76º) were found at the postoperative follow-up, with an average difference of 3.8º (-15.7º-20.2º). 9.4% (6 patients) of degenerative ELS evolved to grade II, and 8 patients needed reoperation for different reasons. In patients with ELS, we found a greater increase in postoperative LL (5.59º) than in patients without ELS (2.61º) (p = 0.08). No statistically significant relationship was found between the behaviour of the LL with the number of decompressed levels (p = 0.43) and the need for reoperation (p = 0.26). Conclusions: According to our study, the technique of posterior decompression without instrumentation of the lumbar spine stenosis is not associated with a decrease of lumbar lordosis parameter. Conversely, there is a slight tendency for LL to increase in cases where a degenerative ELS is present.